Living with Thunder : Exploring the Geological Past, Present, and Future of Pacific Northwest Landscapes - Bishop, Ellen Morris (Book collections on Project MUSE., 2014)
The Pacific Northwest is a region defined by its geology as much as its rugged coastline, drippy westside forests, fertile farms, and canyoned eastside grasslands. These landscapes have been forged by volcanoes, crumpled by faults and sculpted by water and ice. But the Northwest's geologic DNA is rooted in volcanic activity. From the ancient lavas of Washington's Selkirks that freed the planet from a global ice age, to the world-class flood-basalts that dominate the Columbia Basin, to the restless peaks of the High Cascades, the thunder of volcanic eruptions echoes through the ages.